PERAN PERTEMUAN PENINGKATAN KAPASITAS KELUARGA PADA PENGELOLAAN KEUANGAN KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN - Agus Zul bay; Fitri Kumalasari; Fetni; La Ode Maulid (Halu Oleo University, 2024)
This research aims to understand and describe the role of Family Capacity Building Meetings in financial management for Beneficiary Families of the Family Hope Program. Using qualitative descriptive research methods, the data collected consisted of primary data and secondary data. Primary data was obtained through interviews with three informants from PKH HR and 15 PKH KPM, as well as the results of field observations. Meanwhile, secondary data was collected through literature study and supporting literature. The data analysis technique used is qualitative analysis, which includes data collection, data reduction, data presentation, and drawing conclusions, as explained by Miles and Huberman. The findings indicate that PKH human resources understand the objectives and benefits of the P2K2 program, resulting in a significant impact on enhancing the knowledge and financial management skills of KPM PKH. Through P2K2 meetings, KPMs gain additional insights into family financial management. However, challenges remain, as some KPMs struggle with financial management due to the instability of their monthly income.